Corner T-slot antenna at 2.45 GHz for hyperthermia application - Khan A.; Dubey S.K.; Singh A.K. (My University, 2025)
This study focuses on the design and characterization of a novel T-slot antenna for hyperthermia application at 2.45 GHz. The simulation and experimental results demonstrate that the antenna has a resonant frequency of 2.45 GHz, is found to be in good agreement and a gain of −5.1 dBi. The proposed antenna has a dimension of 26 × 26 × 1.6 mm3 with 2.85% BW. The antenna's surface current distribution and specific absorption rate (SAR) are analyzed using numerical simulations, and the results show that the antenna provides an effective heating pattern with low levels of energy deposition in the surrounding healthy tissue. Finally, a proof-of-concept hyperthermia treatment is performed on a tissue-equivalent-liquid (TEL) phantom using the proposed antenna. The proposed T-slot antenna has the potential for use in hyperthermia treatments for cancer therapy, and further studies are required to evaluate its safety and efficacy for clinical use. © 2024 Informa UK Limited, trading as Taylor & Francis Group.